2020
DOI: 10.1088/1755-1315/419/1/012144
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of fall accident in a high-rise building project

Abstract: Fall accident is an accident category that becomes a primary cause of fatal and nonfatal injuries among construction workers worldwide. The objectives of the paper are to report the results of a study investigating 100 reports of fall accidents in the high-rise building project in Indonesia. The study concludes that the impact/consequence of the fall accident mostly occurring involves a fatality, causing death (56%), major injuries, causing permanent physical defect (28%), and minor injuries, causing temporary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…Huang and Hinze [42], for example, found that fall accidents were caused by workers' misjudgement of hazardous conditions, insufficient or non-existent personal protective equipment (PPE), and inoperative safety measures. Arifuddin et al [6] also discovered that poor housekeeping, faulty ladders, or technically inadequate work platforms can lead to falls. Similarly, the Department of Occupational Safety and Health (DOSH) [11] has identified several factors contributing to high-rise construction accidents, such as flawed management systems, ineffective safety policies, a lack of safety awareness, job site circumstances, no safety inspections or signs, and the unique nature of the job site.…”
Section: Accident Causation In High-rise Constructionmentioning
confidence: 99%
“…Huang and Hinze [42], for example, found that fall accidents were caused by workers' misjudgement of hazardous conditions, insufficient or non-existent personal protective equipment (PPE), and inoperative safety measures. Arifuddin et al [6] also discovered that poor housekeeping, faulty ladders, or technically inadequate work platforms can lead to falls. Similarly, the Department of Occupational Safety and Health (DOSH) [11] has identified several factors contributing to high-rise construction accidents, such as flawed management systems, ineffective safety policies, a lack of safety awareness, job site circumstances, no safety inspections or signs, and the unique nature of the job site.…”
Section: Accident Causation In High-rise Constructionmentioning
confidence: 99%
“…Among the 56 fatal accidents, 25 were found to happen due to equipment failure: a drop of a heavy load, such as wire rope damage (11 cases), a lack of safety measures (seven cases), and the illegal use of worktables (seven cases). Among many fatal accidents caused by structural failures, there were many accidents involving human errors; there were many cases that were specified as indirect causes in the accident investigation reports [37]. The remaining 31 accidents were caused by inappropriate factors in the work environment, such as noncompliance with safety procedures.…”
Section: Structural Failure Of Mobile Crane Fatalitiesmentioning
confidence: 99%
“…As indicated in Table 1 , previous research in this area falls into three categories: (i) research related to the causes of construction disasters [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], (ii) research related to an analysis of the weather impact on injury and fatal accidents in construction [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , ...…”
Section: Literature Reviewmentioning
confidence: 99%
“…Earlier work analyzed the causes of injury and fatal accidents in relation to specific weather conditions, such as those in the summer and winter seasons [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Other research analyzed ‘falls’ and ‘slips’ as frequent types of accident which can be affected by weather conditions [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Still others analyzed construction productivity using the predicted mean vote (PMV) by surveying the thermal comfort of construction workers [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%